Do environmental quality, financial inclusion, and good governance ensure the FDI sustainably in Belt and Road countries? Evidence from an application of CS-ARDL and NARDL - JinRu, Long; Qamruzzaman, Md.; Hangyu, Wu; Kler, Rajnish (Frontiers in Environmental Science, 2022)
Domestic capital adequacy and sustainable economic growth are heavily reliant on technological advancement, managerial know-how, and money supply in the economy. In this context, FDI has emerged and is placed at an apex position due to its unprecedented impact on achieving sustainability across the world. The motivation of this study is to scale the effects of good governance, financial inclusion, and environmental quality on inflows of FDI in BRI nations for the period from 1990 to 2020. Several panel econometrical tools have been applied, for example, CDS, CADF, CIPS, CS-ARDL, and NARDL, to investigate the association and explanatory variables elasticity on inflows of FDI in BRI nations. CDS results revealed that research units share common dynamism and second-generation panel unit root test-documented variables are stationary after the first difference. The results of the panel co-integration with an error-correction term confirmed the empirical equation’s long-run association. According to the CS-ARDL assessment, positive and statistically significant impacts have been documented, from financial inclusion, good governance, and environmental quality to FDI inflows. Study findings suggest that governmental effectiveness, easy access to financial services and benefits, and a less-regulated environmental concern economy motivate capital transfer decisions. The asymmetric assessment documented a long-run asymmetric association between FI, GG, EQ, and FDI. Referring to asymmetric shock elasticity, the study disclosed a positive and statistically significant relation to FDI inflows, especially in the long run. The directional causality test documented bidirectional causality running between FI, EQ, GG, and FDI [FI←→FDI; GG←→FDI; and EQ←→FDI] in the short-run.